Plasma fibrinogen concentration predicts the risk of myocardial infarction differently in various parts of Europe: effects of β-fibrinogen genotype and environmental factors - Mannila, Maria Nastase; Silveira, Angela; Hawe, Emma; Eriksson, Per; Aillaud, Marie Françoise; Juhan-Vague, Irene; Yudkin, John; Margaglione, Maurizio; di Minno, Giovanni; Mussoni, Luciana; Tremoli, Elena; Humphries, Steve; Hamsten, Anders; the HIFMECH study group; on-behalf-of (Thrombosis and Haemostasis, 2004)
The propensity to atherothrombotic disease differs in Europe, with high-risk regions located in the North of Europe and lowrisk regions in the South of Europe. The HIFMECH study (Hypercoagulability and Impaired Fibrinolytic function MECHanisms predisposing to myocardial infarction (MI) study) was undertaken to elucidate genetic and environmental mechanisms underlying MI based on investigations of postinfarction patients and healthy individuals recruited from Stockholm, Sweden, London, England (North of Europe), Marseille, France and San Giovanni Rotondo, Italy (South of Europe). In the present report, emphasis was placed on fibrinogen, a multifunctional protein, widely recognized as an independent predictor of atherothrombotic disease. The adjusted plasma fibrinogen concentration was an independent discriminator between cases and controls in London (SOR 3.58; 95% CI 1.31; 9.83), but not in the other centres. Genotyping for six β-fibrinogen promoter single nucleotide polymorphisms was performed of which -249C/T, -455G/A and -854G/A were used in analysis as a consequence of the linkage disequilibrium pattern. Four haplotypes, with similar distribution across Europe, were detected: CGG (46.7%), CAG (20.3%), TGG (18.2%) and CGA (14.8%). A significant haplotype effect on plasma fibrinogen concentration was observed in patients (p <0.001) but not in controls (p = 0.08).The -455G/A genotype related to plasma fibrinogen concentration amongst patients along with centre and IL-6 concentration (together explaining 11.5% of the variation), whereas predictors amongst controls included centre, body mass index, IL-6 and smoking habit (explaining 15.7%). Thus, plasma fibrinogen concentration contributes differently to MI across Europe, and a disease-related stimulus is required to evoke allele-specific regulation of fibrinogen synthesis.
Keywords: Fibrinogen; myocardial infarction; SNPs; haplotype